Association of Aquatic Invertebrates with the Water Quality in the Ponds of Bhaktapur (Swarnadwar, 2024)
Aquatic invertebrates are representative of the health of habitats they live in. This study was conducted to evaluate aquatic invertebrate diversity and relate them with physico-chemical factors in the ponds of Bhaktapur. Rani pokhari, Bhajya pokhari, Na pokhari and Kamal pokhari were selected for the study. Plankton net was swiped out for approximately one minute in each corner of all the ponds. Five subsequent sweeps were taken repeatedly at each site. Invertebrates collected in the net were kept in a plastic container covered with a lid. The collected species were preserved in 70% alcohol. For physico-chemical analysis, water samples were collected from 10cm below the surface water in BOD bottles from each site and taken to the laboratory of Department of Zoology, Bhaktapur Multiple Campus for the further identification and laboratory work. Total 16 species of aquatic invertebrates belonging to five phyla, 10 orders and 16 families were recorded from the ponds of Bhaktapur. Species richness of aquatic invertebrates was found to be 13, 11, four and five in Rani pokhari, Bhajya pokhari, Na pokhari and Kamal pokhari respectively. Phylum Arthropoda was most abundant in all four ponds. The correlation of species richness with physico-chemical parameters showed a positive correlation with water temperature (r = 0.96), electric conductivity (r = 0.98), free carbon dioxide (r = 0.99) and dissolved oxygen (r = 0.51) while the negative correlation with pH (r = -0.83) and alkalinity (r = -0.83). The result obtained is valuable and useful for continuous water quality monitoring activities and the conservation of freshwater fauna in the ponds of Bhaktapur. Further detailed studies on aquatic invertebrates were highly recommended.